BANTUAN LUAR NEGERI WORLD BANK PADA INDONESIA DALAM PROGRAM CORAL REEF REHABILITATION MANAGEMENT PROGRAM-CORAL TRIANGLE INITIATIVE (COREMAP-CTI)FASE III TAHUN 2014 - 2020 - Putri Nur Solichah, (2021)
Indonesia is such an enriching country with its ocean potential resources. Indonesia's coral reefs benefits will increase its economic value, which can gain around US$ 2 million per year by its tourism, fisheries, and coastal area development. However, the coral reefs' existence is threatened. It is caused by natural disasters such as coral bleaching and the impact of human activities by using explosive bombs on their fishing activities. Therefore, Indonesia insists to created a program that promotes the sustainable management and use of coral reefs resources called 'Coral Reefs Rehabilitation and Management Program-Coral Triangle Initiative (COREMAP-CTI). The program has multiple donors and one of the donors is World Bank. This research will be focusing on World Bank's aid (loan and grant). COREMAP-CTI has three phases, each phase has its own main goals and objectives that are related to one another. However, this program has gone through a lot of problems and challenges in its implementation. The implementation of this program is affected by Indonesia's domestic political dynamic. Therefore, the design of the program needs to be adjusted to the regulation of the country. The main problem that affected the implementation of the program is how the Minister of Marine and Fisheries (MMAF) retreat as the Executing Agency, the implementation of law 23/2014, and the COVID-19 pandemic. This research described the form of the World Bank's foreign aid towards Indonesia on the third phase of COREMAP-CTI program from 2014-2020.